Effects of Quercetin on the Growth and Expression of Immune-Pathway-Related Genes in Silkworm (Lepidoptera: Bombycidae). Issue 6 (7th November 2020) - Shi, Guiqin; Kang, Zhaoyang; Ren, Fei; Zhou, Yuan; Guo, Penglei
Abstract: Quercetin is a flavonoid produced as a defense by plants. The effects of 1% quercetin on the growth and development of Bombyx mori were studied. The activities of the enzymes superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), carboxy-lesterase (CarEs), and glutathione S-transferase (GST) were all measured at 24, 48, 72, and 96 h after quercetin exposure. The results show that quercetin induces the activities of antioxidant and detoxification enzymes. With longer exposure times, enzyme activity first increased and then decreased. The relative expressions of AMP (defensin, CecA), the Toll pathway (cactus, Spatzle, and Rel), the IMD pathway (Imd, Fadd, and Dorsal), the JAK-STAT pathway (STAT, HOP, and Pi3k60), and the Melanization gene (DDC and PAH) were analyzed using quantitative polymerase chain reaction (qPCR). The results indicated that long-term exposure to quercetin could inhibit the expression of immune-related pathway genes in silkworms. This suggests that it can inhibit the activities of antioxidant and detoxifying enzymes, thus inhibiting the immune system and affecting the growth and development, resulting in an increase in the death rate in silkworm. This study provides the novel conclusion that quercetin accumulation inhibits the immune system of silkworm and increases its death rate, a result that may promote the development and utilization of better biopesticides that avoid environmental pollution.